2014
DOI: 10.4067/s0717-95022014000400052
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Expression of Visfatin-Positive Cells in the Spleen of Lipopolysaccharide-Stimulated Piglets

Abstract: SUMMARY:The histological changes in the spleen and the immunohistochemical expression of visfatin in lipopolysaccharidestimulated piglets are reported to examine the relation between visfatin and inflammation. The results are as follows: (1) After LPS treated, the spleen displayed thicker capsules and trabecula, the thinner periarterial lymphatic sheath, and the more expandable splenic sinusoid, with an increase in the number of splenic nodules, lymphocytes, ellipsoids of the marginal zone, red blood cells and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Then, we further con rmed the expression changes of the three lncRNAs in liver, spleen, jejunum and thymus of the piglets challenged with LPS at different times (0, 1, 2, 4, 8, 12 and 24 h). The previous studies demonstrated LPS challenge can induce sever in ammation in the piglet model, causing liver injury, intestinal damage and histological changes of spleen [43][44][45][46][47]. Although the three lncRNAs displayed different tissue expression patterns in the piglets, they all shown abundant expression in liver, spleen, jejunum and thymus.…”
Section: Discussionmentioning
confidence: 95%
“…Then, we further con rmed the expression changes of the three lncRNAs in liver, spleen, jejunum and thymus of the piglets challenged with LPS at different times (0, 1, 2, 4, 8, 12 and 24 h). The previous studies demonstrated LPS challenge can induce sever in ammation in the piglet model, causing liver injury, intestinal damage and histological changes of spleen [43][44][45][46][47]. Although the three lncRNAs displayed different tissue expression patterns in the piglets, they all shown abundant expression in liver, spleen, jejunum and thymus.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have demonstrated LPS challenge can induce severe inflammation in the piglet model, causing liver injury, intestinal damage and histological changes of spleen. 42 , 46 In liver tissues, lncRNA ENSSSCT00000047491 expression increased approximately 4- to 33-fold, lncRNA ENSSSCT00000049770 increased 4- to 12-fold and lncRNA ENSSSCT00000051636 increased 9- to 64-fold in response to LPS challenge. In the spleen and jejunum, LPS challenge induced an increase in expression of these lncRNAs with a maximum response of 4-fold increase.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the humoral immune response was enhanced by COPE. It has been suggested that prominent germinal centers are indicative of increases in the population of proliferating B-lymphocytes and stimulation of humoral response [11,12].…”
Section: Discussionmentioning
confidence: 99%